Fitness characteristics of elite and subelite male ice hockey players: A cross-sectional study - Vigh-Larsen, J. F.; Beck, J. H.; Daasbjerg, A.; Knudsen, C. B.; Kvorning, T.; Overgaard, K.; Andersen, T. B.; Mohr, M. (The Journal of Strength and Conditioning Research, 2019)
The purpose was to evaluate fitness profiles in elite (age 23.5 ± 4.4 years) and subelite (age 19.4 ± 3.1 years) male ice hockey players. Twenty teams from the best (n = 164) and second-best (n = 132) Danish ice hockey division were assessed in-season using a field-test battery consisting of off-ice measurements of countermovement jump (CMJ) performance and body composition, as well as performance tests on the ice. These included the submaximal and maximal Yo-Yo intermittent recovery ice hockey tests, level 1 (Yo-Yo IR1-IHSUB and Yo-Yo IR1-IHMAX), the 5-10-5 pro-agility test, and a straight-line sprint test. Elite players were heavier (85.7 ± 8.1 vs. 80.8 ± 10.0 kg, p = 0.05) and had a higher skeletal muscle mass (41.9 ± 3.9 vs. 38.8 ± 4.7 kg, p = 0.05) than subelite players. Moreover, elite players elicited a superior CMJ (50.1 ± 6.1 vs. 44.9 ± 5.4 cm, p = 0.05), agility (4.76 ± 0.17 vs. 4.96 ± 0.22 seconds, p = 0.05), and sprint (4.49 ± 0.16 vs. 4.71 ± 0.19 seconds, p = 0.05) performance. Finally, elite players outperformed subelite players in Yo-Yo IR1-IHSUB (79.7 ± 6.8 vs. 88.0 ± 5.4% HRmax, p = 0.05) and Yo-Yo IR1-IHMAX tests (2,434 ± 414 vs. 1,850 ± 499 m, p = 0.05). Top elite teams performed. 1.1 and 7% better than bottom elite teams on the agility and CMJ test (p = 0.05), whereas differences approached significance for sprint (p = 0.08) and Yo-Yo IR1-IHMAX (p = 0.08) performance in favor of top-tier teams. No differences were observed between forwards and defensemen. In conclusion, elite-level ice hockey requires a high level of fitness in terms of muscle mass and explosive strength, as well as a well-developed high-intensity intermittent exercise capacity. In addition, these demands seem to apply for both forwards and defensemen.